LAYANAN INFORMASI PEREKRUTAN DAN PENYALUR TENAGA KERJA BERBASIS SHORT MESSAGE SERVICE - Sarwindah Indah (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2018)
With the increasing public demand for information and entertainment, the use of SMS media as a means of requesting and distributing information services is very efficient and innovative. For this purpose, businesses and offices that want to provide SMS-based information services require applications that can support this service. MS Workforce Distribution is one of the services to recruit workers through SMS. Besides that, it is also easier to get interview schedules for candidates or job seekers. This application runs after the system receives SMS that enters via mobile as the server. After being processed by a computer, the results will be sent back to the client or candidate who requested via mobile. In addition, there are broadcast systems that are announcements that inform clients or candidates. Java programming is multi-platform which can be used in a variety of System Operations and Windows. With the development of this application, it is expected to help clients or candidates to get the desired information faster.